The Cost of Having Wild Boar : Damage to Agriculture in South-Southeast Sweden - Schön, Tomas (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
In many parts of the world where people engage in farming activities, wildlife is responsible for causing considerable amounts of damage to agriculture thus affecting human economy. Damage to crops is typically caused by ungulates and one species in particular: the Wild boar (Sus scrofa). In Europe compensation paid by different governments amount to several million Euros annually, which is part of the reason why the wild boar is now considered a pest in many parts of the world. In Sweden the wild boar was extinct during the 17th century but has later returned and today the population size has increased dramatically, causing damages to Sweden’s agriculture. Attempts have been made at estimating the cost of these damages however, most of these studies have had a restricted sample sizes and/or considered only a limited geographic range. The central aim of this study was to quantify the damage, and subsequently the cost, caused by wild boar on agricultural crops in the south and south-eastern parts of Sweden. Given previous work done on the subject I expected to find a relationship between field size and damage level. Furthermore the study provided answer to a central methodological question: whether field sampling done post instead of pre harvest was more time efficient yet produced an estimate similar to that of the pre-harvest method. By using estimates of damage levels on three crops gathered in the field and data from Statistics Sweden I computed the total value of wild boar damages. I found that the value of yield loss to wild boar equals 151.8 – 240 million SEK for the year 2012 in the five LRF regions Skåne, Sydost, Jönköping, Södermanland and Mälardalen. Field sampling done post-harvest produced an equally accurate estimate as that of the pre-harvest method at the same time as it is 3.6 times faster (p=0.0625).The wild boar is well established in Sweden and they are here to stay. This calls for further refining of methods to evaluate their damage-causing behavior and both the spatial and temporal characteristics of that behavior if farming is to be considered economically sustainable – and not just for big agricultural corporations.